Platform Design and Innovation Incentives: Evidence from the Product Ratings System on Apple's App Store - Benjamin T. Leyden (Center for Economic Studies and Ifo Institute (CESifo), 2021)
A lack of platform-level competition among digital marketplaces can result in socially inefficient platform design and meaningful welfare losses, even independent of actively anticompetitive behavior. To illustrate the first-order effects platform design can have on competitive outcomes, I investigate how the longstanding design of the product ratings system on Apple's App Store affected innovative behavior by platform participants. I leverage an exogenous change in this system to show that for nearly a decade, the design of the App Store's product ratings system led to less frequent product updating by high-quality products. I provide suggestive evidence that this policy resulted in lost, as opposed to simply delayed, innovation.
Keywords: 330